A survey on medicine consumption in the mega cities of Iran (Italian Journal of Public Health, 2011)
Background: Studying medicine consumption is a significant parameter in the estimation of the health caresystem of a country. This study evaluates the amount of medicine consumption in the mega cities of Iranand indentifies individual factors that influence this consumption.Methods: In this study, a cross-sectional survey of public medicine consumption was directed at randomsamples that counted 628 persons of fifteen years and older in several public places in the mega cities ofIran. The data were collected through questionnaires administered at the public vaccination department ofthe Pasteur institute of Iran in Tehran, and in other public places in Esfahan. A multiple regression modelwas utilized to analyze individual information.Results: Our results showed that 59.4% of the respondents were current medicine consumers. Women usedmedicines less frequently. The rates of medicine consumption among the surveyed population, for dailyand weekly-monthly consumption, were 21.8% and 37.6% respectively. In Iran, it emerged that 52.4% ofthe respondents obtained their medicines, such as acetaminophen antibiotics, and pain-killers, without aprescription.Conclusions: the study clearly showed that more than 53% of the medicine consuming persons undertakeself-treatment. Three factors gender, age and income level are the main factors influencing medicinesconsumed without physicians’ prescription in the mega cities of Iran.
Keywords: medicine consumption; Iran